The spider genus Oecobius in Iran, with description of two new species (Araneae: Oecobiidae). (2nd October 2017) - Zamani, Alireza; Mirshamsi, Omid; Marusik, Yuri M.; Hatami, Mehdi; Maddahi, Hassan
Abstract: A survey of five species belonging to Oecobius Lucas, 1846 occurring in Iran is provided, including two species new to science: O . ilamensis sp. n. (♂) from Ilam Province, western Iran, and O . ferdowsii sp. n. (♂♀) from Khorasan-e Razavi Semnan provinces, Lorestan and Tehran north, northeastern and western Iran. Iranian distribution records of all five species are mapped. http://www.zoobank.org/urn:lsid:zoobank.org:pub:FF3C8ADD-95BD-433E-AB7E-A95907833F10